P01.164 Cognitive and neuropsychological outcome after awake surgery for left frontal and left temporal tumor resection. (19th September 2018) - Kilinc, F; Noack, A; Lortz, I; Seifert, V; Behrens, M; Forster, M
Abstract: Background: Surgery of brain tumors aims, in general, at complete tumor resection. However, persuing this aim, neuropsychological deficits cannot be considered all the time. Due to its importance regarding quality of life and further professional ability, we analysed the influence of left frontal and left temporal brain tumor surgery on patients′ neuro-cognitive performance. Material and Methods: Neuropsychological evaluation was performed pre-operatively in 33 patients who underwent awake surgery for brain tumors in the left inferior frontal gyrus (IFG), the left anterior frontal lobe (ATL) or the left supramarginal gyrus (SMG). Twelve of these patients underwent additional postoperative neuropsychological examination. Evaluation focused on aspects of language, attention, execution as well as working, verbal and visual memory. Results were analysed descriptive. Results: While first testing was carried out in all patients within 1 month before awake surgery, postoperative evaluation was realized in 12 patients 6.47 ± 3.07 months after surgery. Defining test performances within the 25 th and the 75 th percentile as normal, patients with tumors involving the IFG or SMG showed unimpaired. However, in patients suffering from lesions involving the ATL, reduced verbal memory and impaired interference ability was noted preoperatively, recovering to normal after surgery. Thus, removal by awake surgery of lesions involving the IFG, SMG or ATL did not result in long-term neuropsychological impairments. Conclusion: Our results underline the importance of considering cognitive outcome by evaluating neuropsychological deficits in brain tumor patients.